High intact fibroblast growth factor 23 levels associated with low hemoglobin levels in patients on chronic hemodialysis - Fang, Yu-Wei; Wang, Jing-Tong; Lin, Tzu Yun; Lee, Chung-Jen; Jang, Tsrang-Neng; Tsai, Ming-Hsien; Liou, Hung-Hsiang (Frontiers in Medicine, 2023)
Introduction A negative association between C-terminal fibroblast growth factor 23 (cFGF23) and hemoglobin (Hb) levels has been reported in patients with predialysis chronic kidney disease. In dialysis patients, the dominant form of serum FGF23 is intact FGF23 (iFGF23); however, its association with the Hb level remains unclear. Therefore, simultaneously monitoring iFGF23 and cFGF23 levels is crucial. In this study, we investigated the associations between both forms of FGF23 (iFGF23 and cFGF23) and renal anemia in chronic hemodialysis (CHD) patients. Methods We included 166 CHD patients from two hospitals in this cross-sectional, observational study. The primary predictors were serum iFGF23, cFGF23, and iFGF23/cFGF23 levels. The main outcome was the Hb level. Results Among the CHD patients included, 60.8% were men with a mean age of 59.4 ± 12.7 years. In the crude analysis, iFGF23 and iFGF23/cFGF23 levels showed a significant negative association (−0.27, p = 0.004 and −0.22, p = 0.034, respectively) with the Hb level. Even after adjusting for multiple variables (a parsimonious model), every increment of natural log transformation by 1 for (ln)iFGF23 and ln(iFGF23/cFGF23) levels showed a negative correlation with the Hb level (estimate: −0.27 [95%CI: −0.44, −0.10, p = 0.001]; −0.19 [95%CI: −0.37, −0.01, p = 0.042], respectively), whereas both were positively associated with erythropoietin-stimulating agent (ESA) hyporesponsiveness (odds ratio [OR]: [95%CI: 2.30, 1.26–4.17], p = 0.006; 1.95 [95%CI: 1.08–3.50], p = 0.025). Moreover, these abovementioned associations were more dominant in patients with diabetes who used angiotensin receptor blockers. Discussion In conclusion, a negative association between serum iFGF23 or iFGF23/cFGF23 level and the Hb level was observed in our CHD patients. Meanwhile, a higher iFGF23 or iFGF23/cFGF23 level may predispose patients to ESA hyporesponsiveness.